PSORIASIS AS SYSTEM PATHOLOGY - I.V. Kozlova; Yu.V. Shagova; A.L. Bakulev (Саратовский научно-медицинский журнал, 2008)
Psoriasis is one of the most widespread chronic dermatoses which 1-5% of the population of the planet suffers. They consider psoriasis as a systemic disease with not only lesions of skin, but also joints and visceral involvement, as «psoriasis disease». In the review there are discussed pathogenesis of psoriasis, submitted infectious-immunological, genetic, metabolic and neuroendocrine concepts. Changes of digestive, cardiovascular, nervous, hepatobiliary, urinary systems and suppoting-motive apparatus of patients with psoriasis are examined. Methods of treatment of psoriasis are presented. Immunosuppressive and anticytokine therapy is discussed.